Pedagogy in Searching for Other Reason. Towards the Critique of Instrumental Reason - Archacka, Magdalena (INSTED: Interdisciplinary Studies in Education & Society, 2018)
The aim of the article is to seek the genesis of the concept of instrumental reason in pedagogy. Considering a radical critique of the reason conducted by the Frankfurt School an intellectual paradigm of the second half of the 20th century, I reconstruct and analyse philosophical concepts of the "instrumental reason" and Other reason, following the footprints first of T. Adorno and M. Horhheim and then of the second generation of Frankfurters: J. Habermas and H. Schnädelbach. My considerations are accompanied by also by the thought of the Polish philosopher M.J. Siemek. I ponder on the construction of modern social myths and show the way in which the analysed concepts become narrativistic means of building a mythological story, first in philosophy and then in pedagogy. I emphasise the necessity of opening a pedagogical dispute, which will allow to oppose the counter-enlightment tendencies visible in contemporary educational practice.